Clinical and laboratory reatures in different periods of pseudotuberculosis infection in children in the territory of the Novosibirsk region - E. I. Krasnova; G. S. Karpovich; A. V. Vasyunin; I. V. Kuimova; E. N. Kibireva; E. Yu. Ermolovich; V. S. Selivanov; A. V. Zabela; A. E. Shestakov (Лечащий Врач)
In according to the most common definition, pseudotuberculosis is an acute zoonotic infection characterized by a polymorphism of clinical manifestations, prone to recurrent and protracted course. It is known that children suffer from pseudotuberculosis 4-5 times more often than adults. In recent years, there has been a trend towards an increase in recurrent forms of the disease. The lack of a unified clinical classification and clinical guidelines for the management of pediatric patients with pseudotuberculosis infection makes difficult to apply adequate approaches to the diagnosis, treatment and rehabilitation of this infection. The study of the clinical manifestations of pseudotuberculosis in the age aspect, duration and possible outcomes of the disease is a prerequisite for solving this problem. In this regard, prospective monitoring of 60 pediatric patients with a verified diagnosis of «Pseudotuberculosis» who received treatment for this infection in Novosibirsk children’s city Hospital number 3 in 2018-2019 was carried out. The analysis underwent: basic epidemiological data, the effectiveness of the etiological verification of the diagnosis by various methods. Clinical and laboratory features of the course of pseudotuberculosis were identified in the age aspect (by comparing the obtained indicators in two clinical groups: children under 3 years old and children older than 3 years). To assess the condition during the convalescence period, a face-to-face survey of 27 patients and/ or their legal representatives was carried out (in accordance with age characteristics). Patients with a history of pseudotuberculosis with a history of 6 months were selected for questioning.